Silver-catalyzed cascade approach to access fused pyrazolo-naphthyridine and -isoquinoline backbones and investigation of their photophysical properties - Mobarakeh, Fatemeh Abdiyan; Rezaei-Gohar, Mohammad; Amiri, Kamran; Bijanzadeh, Hamid Reza; Rominger, Frank; Balalaie, Saeed (ACS omega, 2025)
We describe a novel approach for synthesizing diverse fused heterocyclic compounds by utilizing a sequential silver(I) catalyzed reaction between readily obtainable N-amidonaphthyridin ylide and dialkyl acetylenedicarboxylates. This method provides an efficient approach for the selective synthesis of tetracyclic ring-fused 1,6-naphthyridine and isoquinoline derivatives, offering exceptional structural diversity. In addition, the title compounds constitute an interesting class of luminophores with tunable emission solvatochromicity.
Veröffentlicht: 04. April 2025
Gesehen am 03.12.2025